PENERAPAN MODEL INQUIRY-PROJECT BASED LEARNING DENGAN STRATEGI READING INFUSION BERBANTUAN GOOGLE CLASSROOM UNTUK MELATIHKAN KETERAMPILAN ABAD 21 DAN PENGUASAAN KONSEP PESERTA DIDIK SMA PADA MATERI GERAK HARMONIK SEDERHANA - Delia Noor Wahidah, - (2020)
Related to face the era of globalization where job competency requires someone who is critical, creative, able to work together, and able to communicate, then learning not only leads to the provision of knowledge but training skills become important. We call these skills as 21st-century skills (KA21). This quasi-experimental study with 100 samples taken randomly from 288 populations in one of the high schools in West Bandung Regency aims to get an overview of the development of KA21 through the application of IPjBL with reading infusion and Google Classroom strategies. The development of KA21 is measured using a rubric that was adopted and adapted from Boss and analyzed using standards developed by Lati. The results showed critical thinking, communication, collaboration, and creative thinking skills of the experimental class had increased. However, improvements in critical thinking, communication, and collaboration skills are lower than in the control class. The conclusion of this research, learning needs to be developed and optimized the use of Google Classroom to get wiser ways to train KA21.